Dissecting global value chains: Evidence from the global automotive industry - Márta Bisztray (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
The potential restructuring of global value chains (GVCs) is a widely discussed question in current debates. At the same time, a proper way of capturing these value chains is challenging. This paper focuses on the automotive industry, using detailed data on firm-to-firm transactions in Hungary, as well as on cross-border sales and purchases. Its aim is twofold, capturing to what extent firms being connected to a GVC differ from other firms in the same industry, and what is the impact of integration into GVCs. Findings suggest that firms being part of GVCs tend to be larger, more productive, foreign-owned and having a higher level of intangible capital. There is some suggestive evidence that entering the GVC has a positive impact on size, productivity and per capita wage for certain firm groups and it is preceeded by increased imports of capital. Finally, there are also differences by employee composition.
Keywords: F23; F61; 330; global value chains; supplier links; automotive industry